Acute phase proteins altered in the plasma of patients with congenital ventricular septal defect. Issue 11 (8th September 2015) - Zhang, Xi; Wang, Kai; Yang, Qin; Wang, Jun; Xuan, Chao; Liu, Xiao‐Cheng; Liu, Zhi‐Gang; He, Guo‐Wei
Abstract : Purpose: Ventricular septal defect (VSD) has intracardiac left‐to‐right shunt and increased pulmonary flow that may affect the acute phase response (APR). We examined the hypothesis that plasma proteins of VSD patients may be altered. Experimental design: 2DE and MS were used to detect differential plasma proteins in VSD patients ( n = 55) and controls ( n = 70). Candidate APR proteins were confirmed by ELISA in new samples. Results: Among three differentially expressed APR proteins from 322 protein spots detected, haptoglobin (0.4 ± 0.04 versus 0.6 ± 0.07 mg/mL; p = 0.016) and serum amyloid P‐component (SAP) (3.8 ± 0.2 versus 6.3 ± 0.8 ng/mL; p = 0.003) were significantly lower and orosomucoid 2 (3.1 ± 0.1 mg/mL versus 2.3 ± 0.1 mg/mL; p < 0.001) was significantly higher in VSD patients than in normal controls. Conclusions and clinical relevance: The plasma concentration of three acute phase proteins, haptoglobin, SAP, and orosomucoid 2 are altered that may reflect inflammation, be associated with decreased innate immune system function, and predispose the VSD patients to vulnerability to infections and pulmonary disease. These three proteins in plasma may also be developed as biomarkers for the function of innate immune system in patients with congenital heart disease.